2020
DOI: 10.1002/ccr3.3085
|View full text |Cite
|
Sign up to set email alerts
|

A case series of a mother and two daughters with a GLI2 gene deletion demonstrating variable expressivity and incomplete penetrance

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Table 3 summarizes all 67 pathogenic CNVs published so far, found in 83 patients with CH, including the present study 5,13,14,16–65 . Forty‐five patients had their PP characterized by sellar MRI, 35 (78%) had EPP, two had absent PP and eight had normal PP.…”
Section: Resultsmentioning
confidence: 91%
“…Table 3 summarizes all 67 pathogenic CNVs published so far, found in 83 patients with CH, including the present study 5,13,14,16–65 . Forty‐five patients had their PP characterized by sellar MRI, 35 (78%) had EPP, two had absent PP and eight had normal PP.…”
Section: Resultsmentioning
confidence: 91%
“…GLI2 was also deleted in Previous case 1, who had normal anterior pituitary gland function and no craniofacial anomalies but had clinodactyly and short stature. Genomic deletions encompassing GLI2 have been reported in nine patients ( 26 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ), and their typical phenotypes were short stature, polydactyly and intellectual disability. Anterior pituitary gland functions were evaluated in five patients: one had panhypopituitarism, but the others had normal anterior pituitary gland function although they had short stature.…”
Section: Discussionmentioning
confidence: 99%
“…GLI2 , SHH , and PTCH1 represent key hedgehog pathway members, which are critical for craniofacial patterning, and variations in these genes have been associated with holoprosencephaly with CL/P ( Roessler et al, 1996 ; Ribeiro et al, 2006 ). The GLI2 gene has been linked to Culler-Jones syndrome and Holoprosencephaly 9 (HPE9), and studies have reported that patients with pathogenic variants of the GLI2 gene demonstrate an autosomal dominant inheritance pattern, variable expressivity and incomplete penetrance ( Elward et al, 2020 ). Bertolacini et al reported the identification of a heterozygous 2-bp deletion (864delCC) in the GLI2 gene in a Brazilian family exhibiting variable manifestations of HPE9 ( Bertolacini et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%